ANALISIS KEBIJAKAN PEMBIAYAAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DAN MADRASAH - Ridho Akbar; Muhammad Syaifuddin; Asmuri Asmuri (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2025)
This study examines the Indonesian government's policies regarding the funding standards for Islamic religious education in schools and madrasahs. Islamic religious education plays a strategic role in shaping students’ character and moral values. However, its implementation faces various challenges, particularly in terms of financial support. Using a literature review approach, this research evaluates key regulations such as Minister of Religious Affairs Decree (KMA) No. 211 of 2011, KMA No. 165 of 2014, and KMA No. 183 of 2019, and analyzes their implementation effectiveness in practice. The findings reveal ongoing disparities in fund allocation, delays in budget disbursement, and insufficient managerial capacity within Islamic educational institutions. Therefore, a comprehensive strategy is needed—encompassing budget transparency, financial management training, community involvement, and collaboration between the government and educational institutions—to ensure a more effective, accountable, and sustainable financing system for Islamic religious education.